Isolation and identification Staphylococcus aureus from Cows ruminal content - Khlil, Hanaa (University of Thi-Qar Journal of Science, 2011)
This study was carried out for isolation of Staphylococcus aureus and identification itfrom Cow΄s ruminal contant through take of specimens and caltured it on (MSA), thepercentage of isolation on this media about 52%, Biochemical tests were done. In biotypingtest the percentage reveled in type C about 61.5% while in type A 38.4% .The specimens gave76% for pigment on Milk agar .While in antibiotic tests appeard sensitive 80.76%.